Professional learning communities impact on student achievement - Hamilton, Jan L.; Saint Mary's College of California. Educational Leadership (Ann Arbor : ProQuest Dissertations & Theses, 2013)
Academic Performance Index (API) is a yearly state performance measure was downloaded for all schools partaking in this study. Elementary, middle and high schools API scores were compared along with specific subgroups: Hispanic, English Learner, African American, socioeconomically disadvantaged, and special education students. Results indicate that Hispanic and English Learner sub groups at the Elementary and Middle school level for Professional Learning Community Schools academic achievement was significant. At the high school level Hispanic and English language Learner sub groups academic achievement was significant for the Non Professional Learning Community schools.
This study examined the impact of the Professional Learning Community model on student achievement in the state of California. Specifically, the study compared student achievement between two school types: Professional Learning Community schools and Non Professional Learning schools. The research utilized existing API scores for California schools compiled by the California Department of Education for the 2007--2008 school year. The Academic Performance Index (API) scores for 136 schools districts in the study was retrieved and examined along with the following additional data: English-language learner, special education status, ethnicity (African American, Hispanic--Latino), and socioeconomically disadvantaged students.
Advisors: Kaetlyn Lad Committee members: Annmarie Maione; Phyllis Metcalf-Turner; Rita Smith.
Source: Dissertation Abstracts International, Volume: 74-11(E), Section: A.
English
Keywords: Educational administration; Educational leadership